Spectral properties of Cr3+ in SrLaGaO4 under high hydrostatic pressure. - Barzowska, J.; Grinberg, M.; Shen, Y.R.; Pajączkowska, A. (Photonics Letters of Poland, 2011)
In this contribution the absorption, excitation and luminescence spectra of SrLaGaO4:Cr3+ at different temperatures and pressures are presented. It was found that luminescence related to 2E->4A2 transition in Cr3+ shifts with pressure to the red region. The pressure shifts of the luminescence related to 2E->4A2 transition and phonon sidebands are estimated. Full Text: PDF References: M. Drozdowski, D. Kasprowicz, A. Pajaczkowska, "Characterization of the elastic and elasto-optic properties of SrLaAlO4 and SrLaGaO4 crystals using the Brillouin scattering method", J. Mol. Struc. 555 119 (2000).[CrossRef] W. Ryba-Romanowski, S. Golab, I. Sokolska, W.A. Pisarski, G. Dominiak-Dzik, A. Pajaczkowska, M. Berkowski, "Anisotropy of optical properties of SrLaAlO4 and SrLaAlO4:Nd", J. Alloy. Comp. 217, 263 (1995).[CrossRef] I. Ruter, H. Muller-Buschbaum, Z. Anorg, "Ein Beitrag über BaLaGaO4 und BaNdGaO4: Verwandte Verbindungen zum ?-K2SO4-Typ sowie über SrLaGaO4 mit K2NiF4-Struktur", Allg. Chem. 58, 119 (1990). [CrossRef] B. Struve, G. Huber, "Laser performance of Cr3+:Gd(Sc,Ga) garnet ", J. Appl. Phys. 57, 45 (1985). [CrossRef] B. Henderson, G.F. Imbush, Optical Spectroscopy of Inorganic Solids (Clarendon, Oxford 1989). M. Grinberg, "Spectroscopic characterisation of disordered materials doped with chromium", Optical Materials 19, 37 (2002). [CrossRef] W. Ryba-Romanowski, S. Golab, W.A. Pisarski, G. Dominiak-Dzik, A. Pajaczkowska, "Investigation of the Cr3+ + sites in SrLaGaO4 crystal", Chem. Phys. Lett. 242 623 (1995). [CrossRef] W. Ryba-Romanowski, S. Golab, A. Gloubokov, A. Pajaczkowska, "Spectroscopic properties of chromium-doped SrLaAlO4 single crystals", Optical Materials 4, 515 (1995). [CrossRef]